Understanding priorities: cervical cancer prevention in senior high school - Windini, Dhaifina Putri; Irsan, Abror; Mardhia, Mardhia (BKM Public Health and Community Medicine, 2023)
Purpose: The study aims to determine the knowledge and priority of prevention issues of health education on senior high school student's knowledge about HPV and cervical cancer. Methods: The research method was quasi-experimental with a one-group pretest-posttest design. The respondents were 42 students from class XI at SMAN 3, Pontianak, Kalimantan Barat. Data analysis used a paired T-test. One of the methods to increase community knowledge, especially adolescents, about HPV and cervical cancer is through health education. Results: Before health education, respondents who had good knowledge were 37 people. After health education, all respondents had good knowledge. The paired T-test showed a significance of p 0,00 (p <0.05). There was an effect of health education on the level of knowledge about cervical cancer before and after intervention. Conclusion: HPV and cervical cancer health education showed effectiveness in increasing knowledge about HPV and cervical cancer in SMAN 3, Pontianak.